Stock Price Prediction Using ARIMA Model - Supriti Khanderwal; Debasis Mohanty (International Journal of Marketing & Human Resource Research, 2021)
This paper presents in depth method of building ARIMA model for stock price prediction. The experimental results obtained with best ARIMA model incontestable the potential of ARIMA models to predict stock costs satisfactory on short-run basis. This might guide investors in stock market to create profitable investment selections. With the results obtained ARIMA models will compete fairly well with rising prediction techniques in short-run prediction. Here we take the data of three sectors from NSE for three years from April 18 to Feb21 and predict the future prices until the end of December 21 using ARIMA model.